Google Zukunftswerkstatt für KMU - Larissa Simon; Rebecca Bilger; Hans-Michael Ferdinand (Markenbrand, 2018)
– This article examines the 'Google Zukunftswerkstatt' ('Google Digital Garage') - a tool invented by Google to support anyone who is interested in learning more about Online Marketing. It is assumed that this tool can have significant positive impacts on the brand presence of small and medium-sized enterprises (SME). On this purpose, Google as a Search Engine as well as the 'Google Zukunftswerkstatt' with a special focus on the manner of its functioning are being introduced. Based on this, some specific lections of the theme library are being investigated. To determine whether the tool can help building up a successful online presence, the experience of a SME manager is used as evidence. This analysis gives indication that the 'Google Zukunftswerkstatt' indeed can help raising knowhow about online possibilities necessary to lead a successful enterprise.
Keywords: 650